(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This research aims to find out the learning strategies used by EFL learners in developing their speaking skills. It employed a qualitative method with triangulation instruments including questionnaires, in-depth interviews, and document analysis. The participants were the EFL learners in the third semester of the English Education Study Program of Tadulako University (n=10), chosen by using the snowball sampling technique. The researcher distributed Language Learning Strategy Questionnaire (LLSQ) to learners to investigate their language learning strategies in speaking skills based on Oxford theory, which consists of six parts of the strategies namely memory strategy, cognitive strategy, compensation strategy, metacognitive strategy, effective strategy, and social strategy. The results of the questionnaire showed that metacognitive has become the most frequently used learning strategy by successful learners with a mean score of 4.22 indicating as strategies are always or almost always used because this strategy help learners regulate their learning, such as paying attention, planning to learn as much as they can and doing self-evaluation to be better in speaking English. This study also found that learners who are successful in speaking skills used a combination of all kinds of learning strategies to improve their speaking skills. Learners have positive improvement in speaking components such as the better pronunciation of English words, use of good grammar, have more vocabulary, fluency in speaking, and can overcome the problems that may occur when they speak English.